CONTINENTAL MUSICOLOGY: DECOLONISING THE MYTH OF A SINGULAR "AFRICAN MUSIC” - Pooley, Thomas M. (International Library of African Music, 2018)
The musical identity of the African continent is sustained in the popular imagination by the idea of its unity. This identity emerges from a constellation of ideas about Africa's distinctiveness constructed by generations of scholars who have diminished its diversity to substantiate the claim that shared principles of musical structure and function in sub-Saharan cultures can be read as ideal types for the continent as a whole. The idea of a singular "African music” is predicated on the notion that African "traditional” music of precolonial origin in sub-Saharan Africa possesses a set of distinctive features that are essential to its identity. Musical cultures as diverse as Aka, Ewe, Shona, Yoruba, and Zulu are subsumed within a singular frame of reference; others that do not possess these features are, by implication, excluded. To make sense of this myth of a singular "African music” we must reckon with the universalising impulse that sustains it. This means interrogating the discursive formations out of which it has been fashioned. Whose interests does it serve? Taking a decolonial perspective on the power dynamics that structure global south-north relations in the academy, this article points to the ways in which the north perpetuates its authority and dominance over the south by subsuming others within its cultural and intellectual ambit. Decolonising "African music” means dismantling the hegemony of "continental musicology” and the myth of a singular "African music” that is its creation.
Keywords: Myth; Decolonisation; Developing countries; African Music; Global South; Continental Musicology